MEDAN CITY AISYIYAH DA'WAH STRATEGY IN SOCIALIZING ANTI-VIOLENCE AGAINST CHILDREN - Siregar, Arobiyah; Walisyah, Tengku (Al-Mubin, 2025)
The rise of cases of violence against children requires a strategic response, one of which is through da'wah that is able to touch public awareness. This study aims to find out the da'wah strategy used by Aisyiyah in socializing the anti-violence movement against children in Medan City. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study show that the da'wah strategy carried out by Aisyiyah Medan City in socializing anti-violence against children includes routine recitation as a medium of education on Islamic values, socialization to Muhammadiyah schools to instill awareness of violence, and a community complaint forum as a forum for reporting and advocacy of violence cases. Through an educational, communicative, and participatory approach, Aisyiyah plays an active role in building public awareness and creating a safe and child-friendly environment